Room Reservation Integration Design to Simplifies Learning Process in University - Triswinadi, Made Widiadnyani; Hediyanto, Umar Yunan Kurnia Septo; Firdaus, Taufiq Maulana (Syntax Literate, 2024)
This research highlights the challenges that developing countries face managing room reservations within institutions. Nigeria and the Philippines lack transparency and real-time information, leading to confusion and inefficiency. Pakistan, the absence of an online system hinders access and raises data security concerns. Indonesia, the manual reservation process wastes time and creates uncertainty. The purpose of this research emphasizes the need for an online room reservation system to address issues such as transparency, real- time information, and efficiency. This research explores and Enterprise Resource Planning (ERP) system as a potential solution. Odoo Quickstart methodology was used to design and implement this solution. The Quickstart was chosen due to its affordability, flexibility and ease of modification. Odoo was chosen for its flexibility and configurability, allowing it to be customized and combined to meet the needs. The rental module in Odoo supports room reservation requirements by providing reservation form, schedule, delivery, and return functions in a single interface. Overall, the results of this study advocate for implementing an online room reservation system to improve the reservation process within educational institutions in developing countries.